Microdosing psilocybin for chronic pain: a case series. Issue 4 (5th September 2022) - Lyes, Matthew; Yang, Kevin H.; Castellanos, Joel; Furnish, Timothy
Abstract : Low-dose psilocybin, a psychedelic serotonergic agonist, may provide analgesic benefits to patients with chronic neuropathic pain with minimal physical or psychotropic side effects. Abstract: Psychedelic serotonergic agonists such as psilocybin have recently been shown to produce sustained benefit in refractory depression, end of life anxiety, and addiction when administered in hallucinogenic doses and coupled with psychotherapy. Although it has been suggested that similar high-dose protocols may help chronic pain conditions, there are few published clinical trials of psychedelics for pain. The use of these agents in subpsychedelic doses for chronic pain management has received even less attention. This case series details the experiences of 3 individuals who have used low-dose psilocybin to manage chronic neuropathic pain. Although the nature and etiology of each patient's pain vary, they share a common experience, including inefficacy of current therapeutics and decreased quality of life. Through self-administration of psilocybin, these patients have achieved robust pain relief with decreased reliance on traditional analgesic medications. Despite varying preparations and uncertain potencies, the analgesic effects for all 3 patients occurred at doses without a psychedelic experience and with minimal cognitive or somatic adverse effects. Furthermore, the efficacy of pain relief and, in some cases, the duration of the effect were magnified when coupled with functional exercise. In addition, in 1 case, repeated dosing seemed to produce increased relief, suggesting a possible long-term plasticity-mediated effect. These commonalities highlight psilocybin's therapeutic potential in the treatment of chronic pain that warrants further investigation.